2001
DOI: 10.1007/s001140100236
|View full text |Cite
|
Sign up to set email alerts
|

Heteropteran chemical repellents identified in the citrus odor of a seabird (crested auklet: Aethia cristatella): evolutionary convergence in chemical ecology

Abstract: The exogenous application of chemical repellents is widespread in birds, but endogenous production is exceedingly rare. We herein report a new class of avian defensive compounds isolated from the feathers and volatile odor of the crested auklet (Aethia cristatella). Mass spectra indicate that n-hexanal, n-octanal, n-decanal, Z-4-decenal and a 12-carbon unsaturated aldehyde comprise the auklet odorant. Octanal and hexanal are also secreted in the repugnant metasternal gland emissions of heteropteran insects and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 22 publications
2
65
0
Order By: Relevance
“…Future chemical and behavioural testing promise to reveal: (i) possible reactions of birds to heterospecific odour; (ii) more subtle conspecific differences between males and females; and (iii) variation between wild and captive populations. With regard to captives, Douglas et al (2001) anecdotally reported that at least one colony (different from that used in this study) might lack odour year-round. Interestingly, the breedingseason plumage we collected from captives exhibited a chemical profile that was generally similar to wild birds (table 1).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Future chemical and behavioural testing promise to reveal: (i) possible reactions of birds to heterospecific odour; (ii) more subtle conspecific differences between males and females; and (iii) variation between wild and captive populations. With regard to captives, Douglas et al (2001) anecdotally reported that at least one colony (different from that used in this study) might lack odour year-round. Interestingly, the breedingseason plumage we collected from captives exhibited a chemical profile that was generally similar to wild birds (table 1).…”
Section: Discussionmentioning
confidence: 86%
“…Third, auklets not only recognized feather odour and two chemical components, but also distinguished between different kinds of odour (figure 3), both of which are prerequisites for chemical communication (Bradbury & Veherencamp 1998). Fourth, the primary courtship display, the 'ruff sniff', involves a strongly scented body region and implicates odour in a specific social context (Jones 1993a Hunter & Jones 1999;Douglas et al 2001), as birds simultaneously rub their bills in the scented nape of their display partner (figure 1). Thus, tangerine odour could function as an olfactory ornament.…”
Section: Discussionmentioning
confidence: 99%
“…1), which emit a pungent citrus-like odor that humans can detect at a considerable distance from breeding colonies [82]. Douglas et al [83] identified the odor constituents as a series of short-chained, saturated and monounsaturated aldehydes, which are corrosive irritants that are volatile and reactive. The authors suggested that the citrus odor might repel ectoparasites since two of the major constituents, hexanal and octanal, are known arthropod repellents.…”
Section: Odorous Feathersmentioning
confidence: 99%
“…Compounds isolated from the feathers of this species include n-hexanal, n-octanal, n-decanal, Z-4-decenal and a 12-carbon unsaturated aldehyde. Octanal and hexanal are ectoparasite repellents and a signal of mate quality at the same time (Douglas et al, 2001). Uropygial gland secretions seem to operate differently in different taxa of ectoparasites.…”
Section: Antiparasitic Substancesmentioning
confidence: 99%